Ekologi Pemerintahan Desa dalam Pengelolaan Dana Desa: Studi tentang Pemerintah Desa dan Masyarakat di Desa Kuta Tualah, Kecamatan Namorambe, Kabupaten Deli Serdang - Deo Agung Haganta Barus; Agustin Pratama Sihotang; Eirene Dahlia Sidabutar; Nasywa Yasmin Purba; Halking Halking (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2026)
This study focuses on analyzing the ecology of village governance in the management of Village Funds and the relationship between village authorities and the community in realizing effective Village Fund governance in Kuta Tualah Village, Namorambe Subdistrict, Deli Serdang Regency. This research employs a qualitative descriptive approach with data collected through observation, interviews, and documentation. The findings indicate that the ecology of village governance is formed through reciprocal interactions between village government, village institutions, and community members involved in the planning, implementation, and monitoring of Village Funds. Village deliberation (musyawarah desa) serves as the primary mechanism for determining development priorities; however, community participation remains suboptimal due to limited time availability, lack of understanding, and low sense of ownership toward village programs. Transparency efforts have been made through the publication of the Village Budget (APBDes) and dissemination of information in village forums, yet these efforts have not been fully accessed by all residents. Coordination among village apparatus—such as the village head, village secretary, treasurer, Village Consultative Body (BPD), Village Community Empowerment Institution (LPM), and Village-Owned Enterprise (BUMDes)generally functions well, although at times affected by sectoral interests and limited administrative capacities. Overall, the governance ecology in Kuta Tualah Village demonstrates a relatively harmonious interaction pattern, yet requires strengthened community participation, improved human resource capacity among village officials, and optimized supervision to ensure more transparent, accountable, and participatory Village Fund management.